(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Patan Academy of Health Sciences School of Medicine (PAHS SOM) has implemented innovative curriculum in line with its mission of producing technically competent and socially responsible doctors. One important strategy is the Clinical Presentation (CP) curriculum. During clinical years undergraduate medical students are taught through CP comprising of 112 common CPs. Each presentation have a schema which is a diagnostic reasoning map. Using the schema, graduates are able to scientifically approach clinical problems, categorize them into diagnostic categories with the help of their basic science knowledge, clinical findings and investigation results to gradually proceed from general and broader categories to more specific categories and finally coming down to the closest possible diagnosis or diagnoses. The diseases or conditions covered by each CPs are outlined while some overlapping and repetitions are expected. The teachings are done as small group sessions with 8-12 students and therefore demands more faculty time. With committed faculties and supportive leadership, successful implementation of the curriculum has been possible at PAHS SOM and the first four batches of students trained in this curriculum have already graduated and serving the society